2023
DOI: 10.1021/acs.biochem.3c00285
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Disordered Flanking Regions Increase the Affinity of a Transcriptional Coactivator Interaction across Vertebrates

Elin Karlsson,
Carl Ottoson,
Weihua Ye
et al.

Abstract: Interactions between two proteins are often mediated by a disordered region in one protein binding to a groove in a folded interaction domain in the other one. While the main determinants of a certain interaction are typically found within a well-defined binding interface involving the groove, recent studies show that nonspecific contacts by flanking regions may increase the affinity. One example is the coupled binding and folding underlying the interaction between the two transcriptional coactivators NCOA3 (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…As a general mechanism, flanking regions can buffer against changes in the binding motif and vice versa, as recently noted for yeast general regulatory factors ( Langstein-Skora et al 2022 ), and several examples of flanking regions that modulate affinity of motif-mediated interactions have been described ( Palopoli et al 2018 ; Staby et al 2021 ; Theisen et al 2021 ; Karlsson et al 2022 ; Karlsson et al 2023 ). Additionally, it has been observed that the flanking regions of short linear motifs often maintain similar amino acid composition and are more conserved compared to disordered regions without an embedded interaction motif ( Chica et al 2009 ).…”
Section: Discussionmentioning
confidence: 87%
“…As a general mechanism, flanking regions can buffer against changes in the binding motif and vice versa, as recently noted for yeast general regulatory factors ( Langstein-Skora et al 2022 ), and several examples of flanking regions that modulate affinity of motif-mediated interactions have been described ( Palopoli et al 2018 ; Staby et al 2021 ; Theisen et al 2021 ; Karlsson et al 2022 ; Karlsson et al 2023 ). Additionally, it has been observed that the flanking regions of short linear motifs often maintain similar amino acid composition and are more conserved compared to disordered regions without an embedded interaction motif ( Chica et al 2009 ).…”
Section: Discussionmentioning
confidence: 87%